El constitutivo de la Escritura, como “Palabra de Dios por Inspiración” - Artola, CP, Antonio M. (Alpha Omega, 2010)
In this assay, prof. Artola exposes the theological triangle of the theology of the Inspiration: Scripture, Inspiration, Hermeneutics, throughout the history of this triad in biblical theology: from Inspiration in the Bible, in Origen and Augustine, in Abelard an d Thomas Aquinas, in Soto, Cano e Báñez, up to the new model in DV 24 of the Second Vatican Council. This new model has to do with the nature of the Bible, as the Word of God, of Inspiration, as motive of its writtenn nature, and of Hermeneutics, as exegesis of the Bible under the action of the same Hoy Spirit, by whom it was written.